External Factors Relating To Morning Schedule Food Leftovers In Current Patients Stay At Donggala Kabelota Hospital - Heni Poendey; Adillah Imansari; Ni Ketut Kariani (Jurnal EduHealth, 2024)
The amount of leftover food obtained by inpatients at the Kabelota Regional Hospital on the breakfast schedule is > 20%. The impact of patient food waste causes losses both in terms of nutritional adequacy per person and costs in terms of purchasing food ingredients. The aim of this study was to analyze external factors related to morning schedule food waste in inpatients at the Kabelota Regional Hospital. This research method uses cross-sectional analytical observation , with a sample size of 50 patients. With primary and secondary data collection techniques.The results of the chi square test analysis showed that there was no significant relationship between the acceptability of food menus and food waste (p>0.05). There is no relationship between portion standards for each type of food and food waste (p>0.05). There is no significant relationship between the timeliness of eating staple food menus, animal side dishes, vegetable side dishes, vegetables and food waste (p>0.05). There was no significant difference between the attitude of the food waiter and the remaining food on the breakfast menu (p>0.05). Conclusion: There is no significant relationship between external factors and the occurrence of food waste in inpatients at the Kabelota Donggala Regional Hospital during the breakfast schedule. Suggestion: For further research, it would be better to analyze the internal factors that cause food waste.